(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This research article overviews the implementation of interlanguage pragmatics in the EFL classrooms which still remains an unresolved question over the last three decades. The flipped classroom model is one of the most innovative teaching methods that recently change the role of teachers and learners, inverting the front-of-class instruction paradigm in favor of active and collaborative classroom learning. To draw the attention to this trend, this article seeks to explore the effectiveness of the flipped classroom for developing Uzbek EFL students’ pragmatic competence and language proficiency by focusing on the comprehension of conversational implicatures during the academic year.